Systolic blood pressure as the mediator of the effect of early menarche on the risk of coronary artery disease: A Mendelian randomization study - Fan, Hsien-Yu; Huang, Yen-Tsung; Chen, Yun-Yu; Hsu, Justin BoKai; Li, Hung-Yuan; Su, Ta-Chen; Lin, Hung-Ju; Chien, Kuo-Liong; Chen, Yang-Ching (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: The risk of coronary artery diseases (CAD) may not be caused by menarche timing directly. Therefore, we aimed to investigate the roles of metabolic factors in explaining the effect of age at menarche on the risk of CAD. METHODS: We identified women with age at menarche and CAD outcomes by using three analytical methods: Mendelian randomization (MR), logistic regression analysis, and Cox proportional hazard regression. First two analyses were performed in the Taiwan Biobank (N=71,923) and the last one analysis was performed in the Chin-Shan Community Cardiovascular Cohort study (N=1,598). We further investigated the role of metabolic factors in mediating the effect of age at menarche on the risk of CAD by using the three complementary methods with mediation analyses. RESULTS: One standard deviation of earlier age at menarche was associated with a 2% higher risk (odds ratio = 1.02, 95% confidence interval [CI] = 1.001–1.03) in the MR analysis, a 11% higher risk (odds ratio = 1.11, 95% CI = 1.02–1.21) in the logistic regression analysis, and a 57% higher risk of coronary artery disease (hazard ratio = 1.57, 95% CI = 1.12–2.19) in the Cox proportional hazard regression. All analysis methods consistently supported the role of systolic blood pressure in mediating this effect. The MR results indicated that 29% (95% CI = 26%–32%) of the effect of genetically predicted earlier age at menarche on the risk of CAD was mediated by genetically predicted systolic blood pressure. CONCLUSIONS: Our results obtained from different analytical methods suggested that interventions aimed at systolic blood pressure lowering can reduce the cases of CAD attributable to earlier age at menarche.